Profitability assessment of the Coffee agroforestry business driven clusters (CaFC) - meter, andrew; Penot, Eric; Vaast, Philippe; Etienne, Hervé; Ponçon, Eric; Bertrand, Benoit (2022)
The profitability assessment is based on data on costs and yields per hectare for the F1 hyrbid variety 'Starmaya' and a local variety. (2022-02-14)